Learning, Course Satisfaction, and Community in the Time of COVID-19: Student Perceptions of the Switch to Emergency Remote Teaching - Christina Iluzada; Tony L. Talbert (Park University, 2022)
This multiple descriptive case study explores how university students responded to their Business Communications course's transitioning to an emergency remote course during the spring semester of 2020. Thirty-nine students completed an end-of-semester questionnaire that recorded their impressions of learning and course satisfaction. Nine of those students also participated in semi-structured interviews about these topics. The data revealed that most students enjoyed and felt they learned more from their in-person course, they missed learning from their peers, and they missed the community that was created during the in-person class sessions that were suspended due to university-sanctioned COVID-19 protocols. This article discusses the need for instructors to integrate continuous interactive community into online courses and the need for universities to provide training for online instructors in this essential component in course preparation and execution.